Cell cycle and epigenetic changes of plant DNA - Shevchenko, G.V. (Вiopolymers and Cell, 2010)
Plants can apply various strategies to minimize environmental impact. One of the strategies is heritable modifications of gene expression which occur without changing original DNA sequence and are known as epigenetic. Signaling pathway Rb-E2F (retinoblastoma (Rb)-transcription factor E2F/DP) connects the cell cycle with factors, modifying structure of chromatin and DNA. It also co- ordinates cell proliferation and differentiation influenced by external stimuli. The article highlights the activity of Rb-E2F/DP signaling pathway and its connection with the epigenetic changes of DNA in plants.